PRELIMINARY CHARACTERIZATION OF HEMAGGLUTININ FROM THE SERUM OF A FRESHWATER FISH CATLA CATLA. - S.S.JAYARAJ (International Journal of Pharma and Bio Sciences, 2014)
A naturally occurring hemagglutinin (HA) was detected in the serum of freshwater fish Catla catla using mammalian erythrocytes (RBC) as indicator cells. The serum gave the highest HA titer with human B RBC. In cross adsorption tests, this RBC type completely adsorbed all HA activities from fish serum. An analysis of the physico-chemical properties of HA showed it to be specifically dependent on the presence of Ca2+ for its activity, irreversibly sensitive to EDTA, stable between pH 6.0 to 8.0 and the thermal stability stable between 10 to 30 0C. Further studies demonstrated that the HA is precipitable by Ammonium sulphate (25, 50 and 75%) but 10% TCA did not show precipitate. The Hemagglutinin - inhibition (HAI) assays performed with 25 carbohydrates revealed that the serum HA was specific for inhibited by GlcNAc, GalNAc, laminarin and lipopolysaccharide (Escherichia coli). Thus this agglutinin to be unique among all the known fish agglutinins